Heart health whispering: A randomized, controlled pilot study to promote nursing student perspective-taking on carers' health risk behaviors - Michelle Lobchuk; Lisa Hoplock; Gayle Halas; Christina West; Cheryl Dika; Wilma Schroeder; Terri Ashcroft; Kathleen Chambers Clouston; Jocelyne Lemoine (BMC, 2018)
Abstract Background Lifestyle counseling is described as a "major breakthrough" in the control of chronic diseases. Counseling can be challenging to nurses due their lack of motivation to counsel, hesitancy to appear non-judgmental, lack of empathy, and lack of time. Nurses voice their need for more training in counseling communication skills. Our main objective was to engage in ongoing development and testing of a promising Heart Health Whispering perspective-taking intervention on nursing students' clinical empathy, perceptual understanding, and client readiness to alter health risk behaviors. Methods In this randomized controlled pilot study, the full intervention (perspective-taking instructions, practice, and video-feedback) and partial intervention (video-feedback only) comprised 24 and 18 nursing students, respectively. Quantitative data were collected with a 10-item pre- and post-intervention clinical empathy tool, a one-item 'readiness to change' health risk behavior tool plus similarity ratings on students' empathic accuracy were calculated. Data were analyzed using Independent Samples t Tests and mixed model ANCOVA models. Students' and actors' evaluative responses toward the intervention phases were collected by handwritten notes, and analyzed using content analysis and constant comparison techniques. Results The main finding was that students in the full intervention group reported greater clinical empathy in the post versus baseline condition. Students underestimated their clinical empathy in comparison to carers' reports in the post-condition. In both intervention groups, carers reported more readiness to change in the post-condition. Carers identified favorable and unfavorable perceptions and outcomes of approaches taken by students. Students desired immediate and direct feedback after the video-dialogue and -tagging exercise. Conclusions Heart Health Whispering is a promising intervention to help educators in basic and continuing education to bolster nurse confidence in empathic conversations on health risk behaviors. This intervention incorporates commonly used strategies to teach empathic communication along with a novel video-analysis application of a perspective-taking task. Student and carer actor comments highlighted the value in opportunities for students to engage in self-evaluation and practicing the empathic process of taking the client's perspective on health risk behaviors.